Investigating the Impacts of Multimedia Presentation Tools on Enhancing Oral Fluency in EFL Classrooms: The Case of Master One Students at the English Department, M’sila - Mrs. Amani GHEZAL (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract As fluency is a critical component of effective communication, there is an increasing need to incorporate innovative methods that support students' speaking skills. The incorporation of digital technologies has opened new avenues for enhancing learners' engagement and advancing spoken fluency. This study investigates the impacts of multimedia presentation tools (PowerPoint, Canva, Google Slides, and audio-visual aids) on enhancing oral fluency among EFL learners and explores the perceptions of both teachers and students regarding their integration in the classroom. Conducted at M’sila University, the study involved 51 Master One EFL students and 07 English teachers; it adopted a descriptive, mixed-methods approach. It gathered data by distributing both structured and semi-structured questionnaires; the structured questionnaire is designed for EFL learners, while the semi-structured questionnaire is administered to EFL teachers. The use of these tools was found to contribute significantly to the development of oral fluency by fostering learner engagement and confidence, reducing speech anxiety, and promoting better content organisation and rehearsal practices, which in turn enhance their overall oral communication. The obtained findings from the current investigation inform both teachers and learners about the benefits and challenges associated with implementing MMPTs in teaching and enhancing students' speaking fluency. The study highlights the practical benefits and challenges of implementing MMPTs and emphasises their role in fostering a more interactive, student-centred learning environment. Accordingly, the research recommends that EFL educators incorporate MMPTs into their teaching strategies and encourage students to participate in relevant training courses to optimise their speaking performance
Keywords: Keywords: Multimedia Presentation Tools (MMPTs); oral fluency; EFL learner; effective communication; digital technology